Heparin-Induced Thrombocytopenia (HIT): An Overview of 230 Patients Treated with Orgaran (Org 10172) - Magnani, H N (Thrombosis and Haemostasis, 1993)
Heparin-induced thrombocytopenia (HIT) with thrombosis occurs in about 1 in 2,000 heparin-treated patients. The arterial or venous thromboses may threaten life and limb hence alternative anticoagulation is needed. Some alternative treatments are possible i.e. LMWH, Ancrod, prostacyclin analogues, Dextran, aspirin and oral anticoagulants, but each has its drawbacks. This report reviews treatment of HIT patients with Orgaran (Org 10172), a low molecular weight heparinoid.Because of its proven antithrombotic activity Orgaran was used to treat 230 HIT patients. One hundred and fifty, nine patients presented with at least one thrombotic problem, which in 88 was due to the heparin use. 92.8% of the patients were considered to have adequately responded to Orgaran during the treatment period. Fifty-nine deaths (25.7%) occurred of which 7 (3.0%) were attributed to Orgaran use. The remaining 52 deaths, 27 of which occurred after Orgaran treatment was successfully terminated, were due to the severe underlying disorders in these patients. These results and the lower cross-reactivity rate (≈10%) with the heparin-induced antibody compared with that of the LMWH (>90%) suggest that although problems remain, Orgaran can be a valuable alternative treatment for patients who suffer from HIT and who require anticoagulation.